2020
DOI: 10.3390/ijerph17249301
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Reminiscences with Virtual Reality Headsets: A Pilot Study with People with Dementia

Abstract: This study aimed to explore the feasibility and effects of promoting reminiscences, using virtual reality (VR) headsets for viewing 360° videos with personal relevance, with people with dementia. A study with a mixed methods design was conducted with nine older adults diagnosed with dementia. Interventions consisted of four sessions, in which the participants’ engagement, psychological and behavioral symptoms, and simulation sickness symptoms were evaluated. Neuropsychiatric symptomatology and quality of life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 40 publications
(74 reference statements)
1
72
0
Order By: Relevance
“…Dedicated devices were used to record 360° videos: Samsung 360-degree cameras equipped with bright f2.0 Lens (Appel et al, 2020;Ashmore et al, 2019), VUZE 360 stereoscopic camera (Evans et al, 2020), GoPro Fusion 360° camera (Coelho et al, 2020), or SP 360° 4K VR Cameras mounted on a tripod (Reeves et al, 2021), and the created videos were post-processed using the package iMovie v10.1.2 (Apple Inc, Ashmore et al, 2019). Different equipment was employed across the interventions, to facilitate the delivery of the immersive experience for the participants: Samsung Gear VR headsets (Appel et al, 2020, Ashmore et al, 201,9 Lindner et al, 2019Tabbaa et al, 2019;Reeves et al, 2021;Veling et al, 2021), Z4 mini-headset (BoboVR; Ashmore et al, 2019;Holmberg et al, 2020), Oculus Go headset (Evans et al, 2020), Oculus Rift VR headset with or without integrated audio system (Hussain, 2018;Coelho et al, 2020;Malihi et al, 2020), Limbix VR headset (Paul et al, 2020), Google Cardboard headset (Ashmore et al, 2019;Lindner et al, 2019), Sennheiser HD 221 headphones to render the sound and to reduce the surrounding acoustic 3 Lundström and Fernaeus (2019) environment (Appel et al, 2020;Veling et al, 2021), and a dictaphone to interview the participants.…”
Section: Methodological Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dedicated devices were used to record 360° videos: Samsung 360-degree cameras equipped with bright f2.0 Lens (Appel et al, 2020;Ashmore et al, 2019), VUZE 360 stereoscopic camera (Evans et al, 2020), GoPro Fusion 360° camera (Coelho et al, 2020), or SP 360° 4K VR Cameras mounted on a tripod (Reeves et al, 2021), and the created videos were post-processed using the package iMovie v10.1.2 (Apple Inc, Ashmore et al, 2019). Different equipment was employed across the interventions, to facilitate the delivery of the immersive experience for the participants: Samsung Gear VR headsets (Appel et al, 2020, Ashmore et al, 201,9 Lindner et al, 2019Tabbaa et al, 2019;Reeves et al, 2021;Veling et al, 2021), Z4 mini-headset (BoboVR; Ashmore et al, 2019;Holmberg et al, 2020), Oculus Go headset (Evans et al, 2020), Oculus Rift VR headset with or without integrated audio system (Hussain, 2018;Coelho et al, 2020;Malihi et al, 2020), Limbix VR headset (Paul et al, 2020), Google Cardboard headset (Ashmore et al, 2019;Lindner et al, 2019), Sennheiser HD 221 headphones to render the sound and to reduce the surrounding acoustic 3 Lundström and Fernaeus (2019) environment (Appel et al, 2020;Veling et al, 2021), and a dictaphone to interview the participants.…”
Section: Methodological Characteristicsmentioning
confidence: 99%
“…Although in small percentages, several symptoms associated with motion sickness were consistently reported across studies. More specifically, a number of participants with dementia manifested a slight increase in the sickness symptoms, with two cases of eyestrain and fullness of head, one case of blurred vision and one case of burping (Coelho et al, 2020), two participants with psychiatric disorders stopped using VRelax due to nausea and dizziness (Veling et al, 2021), and the participant in the case study by Paul et al (2020) reported symptoms of nausea, general discomfort, stomach awareness, sweating, increased salivation, vertigo, and dizziness, especially during the adrenaline activities. Some authors provided suggestions about the possible feature of the immersive 360° videos that may generate motion sickness, such as incongruent images or a mismatch between vestibular and visual cues (Evans et al, 2020;Nason et al, 2020;Paul et al, 2020), the subtle impression that the user is looking at the image through a screen, generated by a less sophisticated technology, or the illusion that the image moves, while the user remained in the same position (Paul et al, 2020).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple scenes can also be presented in a short time and randomly presented in a sequence, thus breaking the restrictions of time and space and being conducive to multi-sensory experiments and the collection of physiological data [68]. VR technology has also been applied in mental health education [69]; the prevention, assessment, and intervention of mental illness [70][71][72]; in the medical field [73,74]. Existing studies have confirmed that VR technology can successfully treat delusions, hallucinations, and other psychiatric symptoms, as well as improving the effectiveness and generality of cognitive and social skills, with the recognition that immersive VR therapy is safe, acceptable, and has a long-term effect [75].…”
Section: The Psychological Application Of Virtual Reality (Vr) Technologymentioning
confidence: 99%
“…Long-term use of the app reduced symptoms of psychological symptoms of dementia (BPSD). In the later study, the authors (Coelho et al, 2020 ) used virtual reality (VR) headsets to allow people with dementia to watch videos with personal relevance to facilitate recall. It was found that most participants enjoyed themselves and often spontaneously shared memories related to the videos.…”
Section: Introductionmentioning
confidence: 99%